Bearing Capacity Analysis of Bridge Foundation Based on Cone Penetration Test Data and Soil Parameters Data - Muhammad Yunus; Zahrin F. Syahdinar (Logic : Jurnal Rancang Bangun dan Teknologi, 2019)
One that deserves the attention of planners in designing a bridge structure is the design of the substructure. This is due to the fact that the structure below determines the quality and service life of a bridge and at present many cases of bridge structure failures are caused by failures of the substructure in holding the load acting on the bridge The aim of this research to test the characteristics of the soil and calculate bearing capacity of the foundation based cone penetration testing data and soil parameters at the Aifa bridge construction field in Fafurwar District, Teluk Bintuni Regency, West Papua Province. From the results of testing the soil characteristics in the laboratory, the type of soil at point 1 is the type of good to bad graded sand soil (SW-SP) with a water content of 17.72%, specific gravity 2.98, liquid limit (LL) = 16,746% included in the non-plastic category. While the location of point 2 is obtained from good to bad graded sand soil type (SW-SP) with a water content of 28.52%, specific gravity 2.73, liquid limit (LL) = 16.746% including the non-plastic category. To analysis of the calculation of the bearing capacity of the foundation Aifa bridge using data from the sondir test results for point 1 was obtained allowable bearing capacity (Qall) is 4.610,44 kN and for point 2 was obtained allowable bearing capacity (Qall) is 3.598,43 kN. For calculating bearing capacity of the foundation using soil parameter data for point 1 was obtained bearing capacity allowable (Qall) is 2.209,93 kN and for point 2 was obtained allowable bearing capacity (Qall) is 655,41 kN